2018
DOI: 10.1002/ece3.4068
|View full text |Cite
|
Sign up to set email alerts
|

Studying the quantity component of seed dispersal effectiveness from exclosure treatments and camera trapping

Abstract: The quantity component of effectiveness of seed dispersal by animals is determined by two events: fruit removal (intensity of the interaction) and animal visitation to the plant (frequency of interactions). Considering dispersal of Prosopis flexuosa seeds as case study, this work aimed at investigating the strengths and weaknesses of the two methods for assessing the quantity component of seed dispersal effectiveness: exclosures and camera traps. Prosopis fruits were offered for 48 hr. Exclosure treatments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Identifying animal seed removers using camera traps is a common practice in ecological research on seed dispersal (Blackham & Corlett, 2015; Campos et al., 2018; Christianini & Galetti, 2007; Cramer et al., 2007; da Silva et al., 2011; Dai et al., 2018; Galetti et al., 2015; Iob & Vieira, 2008; Razafindratsima, 2017; Seufert et al., 2010; Ssali et al., 2018). Several studies have used camera traps to attribute single events of seed removal to particular animal species (Brown et al., 2016; Jansen et al., 2012; White et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying animal seed removers using camera traps is a common practice in ecological research on seed dispersal (Blackham & Corlett, 2015; Campos et al., 2018; Christianini & Galetti, 2007; Cramer et al., 2007; da Silva et al., 2011; Dai et al., 2018; Galetti et al., 2015; Iob & Vieira, 2008; Razafindratsima, 2017; Seufert et al., 2010; Ssali et al., 2018). Several studies have used camera traps to attribute single events of seed removal to particular animal species (Brown et al., 2016; Jansen et al., 2012; White et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Lama guanicoe and Rhea americana) and non-native animals (e.g. Lepus europaeus, Sus scrofa, Equus asinus and Bos taurus; Campos and Ojeda, 1997;Campos et al, 2008Campos et al, , 2011Campos et al, , 2018Campos and Velez, 2015). On the other hand, small rodents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Pernetta 1976), so they better tolerate wet, acidic sites where earthworms are scarce. Thus, in acid peatland and upland heathland sites across Northern England, Butterfield et al (1981) found pygmy shrews to be five times more abundant than were common shrews. In unmodified bog plots in our study, we detected pygmy shrews during ten individual camera trap deployments compared to four for common shrews.…”
Section: Discussionmentioning
confidence: 88%